A PEDOT / ZnIn2S4 organic-inorganic hybrid photoelectric material and preparation method thereof

By using ionic liquid to regulate the surface morphology of ZnIn2S4 and the sensitization effect of PEDOT, a high-regular PEDOT/ZnIn2S4 organic-inorganic hybrid photoelectric material is formed, which solves the problem of insufficient conductivity of existing photoelectric materials and achieves efficient photoelectric conversion and stability.

CN113921718BInactive Publication Date: 2025-04-25WUHAN UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202111162813.7
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2021-09-30
Publication Date
2025-04-25
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

In the application of existing photoelectric materials in the field of photoelectrochemical sensing, due to the problem of electron-hole recombination in organic conjugated polymers, the conductivity is insufficient and cannot meet the rapid development needs of the new generation of organic photoelectric devices.

Method used

Ionic liquid is used as a morphological regulator, and by adjusting the surface morphology of the inorganic material ZnIn2S4, combined with the sensitization effect of the organic material PEDOT, a high-regular PEDOT/ZnIn2S4 organic-inorganic hybrid photoelectric material is formed, and a PEDOT film is prepared by electrochemical polymerization.

Benefits of technology

It significantly improves the conductivity and photoelectric conversion efficiency of photoelectric materials, enhances the sensitivity enhancement effect of PEDOT on ZnIn2S4, achieves high photocurrent and stability, and is suitable for the field of photoelectric sensing.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN113921718B_ABST
    Figure CN113921718B_ABST
Patent Text Reader

Abstract

The present invention relates to the technical field of preparation of organic-inorganic hybrid photoelectric materials, and in particular to a PEDOT / ZnIn2S4 organic-inorganic hybrid photoelectric material and a preparation method thereof, comprising a ZnIn2S4 inorganic material, a PEDOT organic material deposited on the surface of the ZnIn2S4 inorganic material, and a doped 1-hydroxyethyl-3-methylimidazolium cation [HOEMIM] + and BF4 – PF6 – NTf2 – At least one of the anions. The present invention uses ionic liquid as a morphology regulator to adjust the surface morphology of the inorganic material ZnIn2S4, and then adjust its photoelectric properties, providing a new idea for the preparation of adjusting the performance of inorganic photoelectric materials; the organic material PEDOT has a very significant sensitization effect on the inorganic material ZnIn2S4, and the PEDOT obtained by changing the ionic liquid shows different degrees of sensitization effect on ZnIn2S4.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of preparation of organic-inorganic hybrid photoelectric materials, and in particular to a PEDOT / ZnIn2S4 organic-inorganic hybrid photoelectric material and a preparation method thereof. Background Art

[0002] Photoelectrochemical (PEC) sensing technology has attracted a lot of research due to its significant advantages such as simple detection equipment, fast response speed and high sensitivity. These advantages make PEC sensing technology widely used in biological, chemical and environmental fields. Generally, the performance of optoelectronic materials indirectly affects the sensitivity of PEC analysis. So far, the research on optoelectronic materials in PEC sensing is mainly based on inorganic-inorganic composite materials, including type II, Z-type and S-type heterojunctions and emerging homojunctions, while there are fewer studies based on organic-inorganic hybrid materials. This is because the serious electron-hole recombination in organic conjugated polymers has hindered the development of organic-inorganic optoelectronic materials.

[0003] Doping is one of the strategies to solve the above problems. Because doping can improve the electron or hole transport ability of organic conjugated polymers, thereby increasing their conductivity and reducing the recombination of electrons and holes, PEDOT:PSS prepared with PSS (poly-4-styrene sulfonate) as a dopant is one of the most important and successful conductive polymers. Although the doping of PSS has broadened the application field of PEDOT, the low conductivity of PEDOT:PSS film can no longer meet the needs of the rapid development of a new generation of organic optoelectronic devices, so the development of other doping materials is of great significance. Some researchers have demonstrated that the use of dopants with hole transport properties, such as lignin sulfonic acid (SL) and alkyl-bridged lignin sulfonic acid (ASL), grafted sulfonated acetone formaldehyde lignin (GSL) and sulfonated butyl phenolic resin (BSPF), can improve the hole transport performance, conductivity and photoelectric conversion efficiency of PEDOT. In addition, Kim et al. reported that PEDOT prepared with imidazolyl poly(ionic liquid) as dopant (PEDOT:PIL) is a unique polymer hole injection material that can improve the device lifetime of organic light-emitting diodes (OLEDs). Izarra et al. showed that the most effective IL anions can maintain the highest number of charge carriers uniformly distributed along the PEDOT backbone to further enhance conductivity, provided that they remain in the PEDOT domains after ion exchange. These results show that ionic liquids can also be used as dopants to improve the conductivity of PEDOT.

[0004] Constructing a pn heterojunction is another effective strategy. Because the internal electric field established in the pn heterojunction can effectively separate the photogenerated electron-hole pairs by promoting the reverse motion of photogenerated electrons and holes, further improving the photocatalytic performance, some inorganic semiconductors that form pn heterojunctions with PEDOT have been reported, including TiO2 nanorod arrays, ZnO nanorods, and Ga2O3 microwires. They are highly ordered one-dimensional micro-nanostructures with high specific surface areas, providing more direct and effective electron transport channels for photogenerated carriers, further reducing the charge recombination of organic-inorganic pn heterojunction materials. Compared with the above one-dimensional semiconductors, three-dimensional ZnIn2S4 flower-like microspheres with uniform and ordered cross-linked nanosheet arrays may be a good choice. Since the cross-linked nanosheets act as an effective light scattering unit, the absorption of light is improved, and in the continuous interface formed with other materials, the carriers are non-localized and the transmission is more favorable. It has been reported in the literature that PEDOT-modified ZnIn2S4 can enhance the transfer of photogenerated electrons and holes and reduce the recombination between them. Unfortunately, there is no research on whether a pn heterojunction is formed between them. Similarly, the reported ZnIn2S4-based pn heterojunction based on organic-inorganic materials is also very rare. Therefore, studying the photoelectrochemical properties of PEDOT / ZnIn2S4 is of great significance to enrich organic-inorganic hybrid materials.

[0005] Ionic liquids (ILs) are known for their unique physicochemical properties, including thermal stability, nonvolatility, and high ionic conductivity, which have made them extremely influential in scientific research fields such as inorganic chemistry. Based on steric hindrance, electrostatic interaction, solvation force, and viscosity stabilization, ILs can form protective layers to control the morphology of inorganic materials and change the properties of materials. The use of ionic liquids as precursors, templates, and solvents allows inorganic materials to have customized sizes, morphologies, and functions, which are difficult to obtain using traditional solvents. In addition, inorganic materials regulated by ionic liquids also have faster electron transfer rates, which is due to the retention of some ionic liquids in the synthesized inorganic materials. In recent years, researchers have prepared SnS2 microspheres, hollow CoFe2O4 microspheres, and SnO microspheres using appropriate ionic liquids. Our previous work has demonstrated that ZnO nanorod arrays prepared using [BMIM]Cl ionic liquid instead of traditional KCl as the supporting electrolyte are more uniform and ordered, and have larger photocurrents. Therefore, it is feasible to use ionic liquids (ILs) to regulate ZnIn2S4 flower-shaped microspheres to have uniform and ordered cross-linked nanosheet arrays on their surfaces and accelerate electron transfer. Summary of the invention

[0006] One of the purposes of the present invention is to provide a PEDOT / ZnIn2S4 organic-inorganic hybrid photoelectric material with high morphology regularity. Ionic liquid acts as a morphology regulator to adjust the surface morphology of the inorganic material ZnIn2S4, thereby adjusting its photoelectric properties. The organic material PEDOT has a very significant sensitizing effect on the inorganic material ZnIn2S4.

[0007] The second object of the present invention is to provide a PEDOT / ZnIn2S4 organic-inorganic hybrid photoelectric material and a preparation method thereof, which has a simple preparation process and is easy to adjust.

[0008] The solution adopted by the present invention to achieve one of the purposes is: a PEDOT / ZnIn2S4 organic-inorganic hybrid photoelectric material, including a ZnIn2S4 inorganic material, a PEDOT organic material deposited on the surface of the ZnIn2S4 inorganic material, and a doped 1-hydroxyethyl-3-methylimidazolium cation [HOEMIM] + and BF4 – PF6 – NTf2 – At least one of the anions.

[0009] Preferably, the PEDOT / ZnIn2S4 hybrid material in the PEDOT / ZnIn2S4 organic-inorganic hybrid photoelectric material has a pn heterojunction structure.

[0010] Preferably, the ZnIn2S4 inorganic material is in the shape of a flower ball, and the deposition thickness of the PEDOT organic material is 20-40 nm.

[0011] The solution adopted by the present invention to achieve the second purpose is: a method for preparing the PEDOT / ZnIn2S4 organic-inorganic hybrid photoelectric material, comprising the following steps:

[0012] a. Dissolve the zinc salt, indium salt and ionic liquid in water and stir at room temperature until uniformly mixed to obtain a mixed solution;

[0013] b. Add thioacetamide (TAA) to the solution obtained in step a and continue stirring at room temperature until the mixture is uniformly mixed;

[0014] c. The solution obtained in step b is reacted at 140-180°C and then cooled naturally;

[0015] d. washing and drying the solid product obtained in step c to obtain an inorganic material;

[0016] e. preparing an electrolyte of EDOT and ionic liquid;

[0017] f. Electrochemically polymerizing PEDOT using the electrolyte prepared in step e on the surface of the electrode on which the inorganic material was drop-coated, to prepare PEDOT / ZnIn2S4 organic-inorganic hybrid photoelectric material.

[0018] Preferably, in step a, in the mixed solution, Zn 2+ WithIn + The molar ratio of Zn is 1:2. 2+ The molar ratio of the deionized liquid to the ionic liquid is 1:10-40, and the concentration of the deionized liquid in the system is 10-40 mmol L -1 .

[0019] Preferably, in step a, the ionic liquid is at least one of [HOEMIM]NTf2, [HOEMIM]PF6, and [HOEMIM]BF4.

[0020] Preferably, in step b, thioacetamide and Zn 2+ The molar ratio is 4:1.

[0021] Preferably, in step e, the solvent used to prepare the electrolyte is anhydrous acetonitrile, the molar ratio of the ionic liquid to EDOT in the electrolyte is 1-6:5, and the concentration of EDOT is 3-7 mmol / L.

[0022] Preferably, in step e, the ionic liquid is at least one of [HOEMIM]NTf2, [HOEMIM]PF6, and [HOEMIM]BF4.

[0023] Preferably, in step f, the specific method of electrochemically polymerizing PEDOT is to immerse the electrode coated with inorganic material in the electrolyte prepared in step e, and use cyclic voltammetry to perform 5-9 cycles of electrochemical polymerization in the range of -0.2-1.7V to prepare PEDOT, thereby obtaining PEDOT / ZnIn2S4 organic-inorganic hybrid photoelectric material.

[0024] In the present invention, the ionic liquid plays a role in regulating the morphology and photoelectric properties. The addition of the ionic liquid has the following advantages. First, the morphology of PEDOT and ZnIn2S4 can be regulated. The ionic liquid can form a protective layer through steric hindrance, electrostatic effect, solvation and viscosity stabilization to control the morphology of inorganic materials and change the properties of the materials. In addition, the ionic liquid retained in the inorganic material can also accelerate the electron transfer. Second, the ionic liquid as a dopant can accelerate the transmission of photogenerated holes in organic materials, improve conductivity, and thus improve the sensitization effect of PEDOT on the inorganic material ZnIn2S4.

[0025] The present invention has the following advantages and beneficial effects:

[0026] 1. The PEDOT / ZnIn2S4 organic-inorganic hybrid photoelectric material of the present invention adopts ionic liquid as a morphology regulator to adjust the surface morphology of the inorganic material ZnIn2S4, and then adjust its photoelectric properties, which provides a new idea for the preparation of adjusting the performance of inorganic photoelectric materials; the organic material PEDOT has a very significant sensitization effect on the inorganic material ZnIn2S4, and the PEDOT obtained by changing the ionic liquid shows different degrees of sensitization effect on ZnIn2S4, thus obtaining PEDOT / ZnIn2S4 organic-inorganic hybrid photoelectric materials with different photocurrents, which are suitable for use in the field of photoelectric sensing, among which the sensitization effect of [HOEMIM]NTf2-PEDOT on [HOEMIM]BF4-ZnIn2S4 is the most significant, which is about 78 times, the highest reported in the literature.

[0027] 2. In the PEDOT / ZnIn2S4 organic-inorganic hybrid photoelectric material of the present invention, the ionic liquid can accelerate the electron transfer rate of the inorganic material and improve the hole transport capacity of the organic material. When excited by light, the PEDOT / ZnIn2S4 organic-inorganic hybrid photoelectrochemical material exhibits excellent photoelectric properties.

[0028] 3. The PEDOT / ZnIn2S4 organic-inorganic hybrid photoelectric material of the present invention has an orderly morphology and high regularity; PEDOT has a significant sensitization effect on ZnIn2S4; the sensitization multiple and photocurrent change with the change of ionic liquid; and the stability is good.

[0029] 4. The preparation method of the present invention first synthesizes ionic liquid regulated ZnIn2S4 by a one-step hydrothermal method, and then replaces the traditional supporting electrolyte with ionic liquid to prepare PEDOT film on the surface of ZnIn2S4 by electrochemical polymerization, thereby obtaining PEDOT / ZnIn2S4 organic-inorganic hybrid photoelectric material. It has the highest sensitization effect reported in the literature. In addition, the method is simple to operate and low in cost. BRIEF DESCRIPTION OF THE DRAWINGS

[0030] Figure 1 The XRD patterns of ZnIn2S4 regulated by different ionic liquids and unregulated ZnIn2S4 obtained in Examples 1, 2 and 3 of the present invention;

[0031] Figure 2 It is a scanning electron microscope image of ZnIn2S4 regulated by different ionic liquids and unregulated ZnIn2S4 obtained in Examples 1, 2 and 3 of the present invention;

[0032] Figure 3 The photocurrent response diagrams of ZnIn2S4 regulated by different ionic liquids and unregulated ZnIn2S4 obtained in Examples 1, 2 and 3 of the present invention;

[0033] Figure 4 These are scanning electron microscope images of [HOEMIM]BF4-PEDOT / [HOEMIM]BF4-ZnIn2S4, [HOEMIM]PF6-PEDOT / [HOEMIM]BF4-ZnIn2S4, [HOEMIM]NTf2-PEDOT / [HOEMIM]BF4-ZnIn2S4, and LiClO4-PEDOT / [HOEMIM]BF4-ZnIn2S4 obtained in Examples 4, 5, and 6 of the present invention;

[0034] Figure 5 These are the photocurrent response diagrams of [HOEMIM]BF4-PEDOT / [HOEMIM]BF4-ZnIn2S4, [HOEMIM]PF6-PEDOT / [HOEMIM]BF4-ZnIn2S4, [HOEMIM]NTf2-PEDOT / [HOEMIM]BF4-ZnIn2S4, LiClO4-PEDOT / [HOEMIM]BF4-ZnIn2S4 and [HOEMIM]BF4-ZnIn2S4 obtained in Examples 4, 5 and 6 of the present invention;

[0035] Figure 6 6A) and Mott-Schottky curves (6B) of the current-potential linear scanning curve of [HOEMIM]NTf2-PEDOT / [HOEMIM]BF4-ZnIn2S4 prepared in Example 6 of the present invention;

[0036] Figure 7 These are the photocurrent response diagrams of [HOEMIM]NTf2-PEDOT / [HOEMIM]PF6-ZnIn2S4, [HOEMIM]NTf2-PEDOT / [HOEMIM]NTf2-ZnIn2S4, [HOEMIM]PF6-ZnIn2S4, and [HOEMIM]NTf2-ZnIn2S4 obtained in Examples 7 and 8 of the present invention. DETAILED DESCRIPTION

[0037] For a better understanding of the present invention, the following examples are provided to further illustrate the present invention, but the present invention is not limited to the following examples.

[0038] Example 1

[0039] (i) 1.0 mmol ZnSO4·7H2O, 2 mmol InCl3·4H2O, and 20 mmol [HOEMIM]NTf2 ionic liquid were dissolved in 50 mL deionized water and magnetically stirred at room temperature for 30 min;

[0040] (ii) Add 4.0 mmol of thioacetamide (TAA) to the above solution and stir magnetically at room temperature for 30 minutes.

[0041] (iii) Add the above solution into the reaction kettle, move the reaction kettle into an oven and heat at 160° C. for 2 hours.

[0042] (iv) The reaction vessel was cooled at room temperature, the obtained solid was washed and freeze-dried to obtain [HOEMIM]NTf2-ZnIn2S4 inorganic material, and 10 mg / mL aqueous solution was prepared respectively.

[0043] Example 2

[0044] (i) 1.0 mmol ZnSO4·7H2O, 2 mmol InCl3·4H2O, and 20 mmol [HOEMIM]PF6 ionic liquid were dissolved in 50 mL deionized water and magnetically stirred at room temperature for 30 min;

[0045] (ii) Add 4.0 mmol of thioacetamide (TAA) to the above solution and stir magnetically at room temperature for 30 minutes.

[0046] (iii) Add the above solution into the reaction kettle, move the reaction kettle into an oven and heat at 160° C. for 2 hours.

[0047] (iv) The reaction vessel was cooled at room temperature, the obtained solid was washed and freeze-dried to obtain [HOEMIM]PF6-ZnIn2S4 inorganic material, and 10 mg / mL aqueous solution was prepared respectively.

[0048] Example 3

[0049] (i) 1.0 mmol ZnSO4·7H2O, 2 mmol InCl3·4H2O, and 20 mmol [HOEMIM]BF4 ionic liquid were dissolved in 50 mL deionized water and magnetically stirred at room temperature for 30 min;

[0050] (ii) Add 4.0 mmol of thioacetamide (TAA) to the above solution and stir magnetically at room temperature for 30 minutes.

[0051] (iii) Add the above solution into the reaction kettle, move the reaction kettle into an oven and heat at 160° C. for 2 hours.

[0052] (iv) The reaction vessel was cooled at room temperature, the obtained solid was washed and freeze-dried to obtain [HOEMIM]BF4-ZnIn2S4 inorganic material, and 10 mg / mL aqueous solutions were prepared respectively.

[0053] Figure 1The XRD patterns of ZnIn2S4 regulated by different ionic liquids and unregulated ZnIn2S4 obtained in Examples 1, 2 and 3 of the present invention are shown in FIG. As can be seen from the figure, the ZnIn2S4 prepared by the present invention is a pure hexagonal crystal, and has the same crystal structure as ZnIn2S4 (a) prepared by the traditional method.

[0054] Figure 2 The scanning electron microscope images of ZnIn2S4 regulated by different ionic liquids and unregulated ZnIn2S4 obtained in Examples 1, 2, and 3 of the present invention are shown. As can be seen from the figure, compared with ZnIn2S4 prepared by the traditional method, the surface morphology regularity of the prepared [HOEMIM]NTf2-ZnIn2S4, [HOEMIM]PF6-ZnIn2S4, and [HOEMIM]BF4-ZnIn2S4 gradually increases, among which [HOEMIM]BF4-ZnIn2S4 has the most regular cross-linked nanosheet array morphology characteristics.

[0055] Figure 3 It is the photocurrent response diagram of ZnIn2S4 regulated by different ionic liquids and unregulated ZnIn2S4 obtained in Examples 1, 2, and 3 of the present invention. It can be seen from the figure that ZnIn2S4 with different photocurrent sizes can be obtained by using different ionic liquids as morphology regulators, indicating that the introduction of ionic liquids can adjust the photoelectric properties of the inorganic material ZnIn2S4. The photocurrents of the prepared [HOEMIM]NTf2-ZnIn2S4, [HOEMIM]PF6-ZnIn2S4, and [HOEMIM]BF4-ZnIn2S4 gradually decrease, among which [HOEMIM]BF4-ZnIn2S4 has the smallest photocurrent.

[0056] Example 4

[0057] (i) preparing an electrolyte containing EDOT and [HOEMIM]BF4, wherein the solvent used is anhydrous acetonitrile, the concentration of EDOT is 5 mmol / L, and the concentration of [HOEMIM]BF4 is 2 mmol / L;

[0058] (ii) 5 μL of [HOEMIM]BF4-ZnIn2S4 prepared in Example 3 was drop-coated on the surface of a clean glassy carbon electrode (GCE) and dried;

[0059] (iii) Immerse the dried electrode [HOEMIM]BF4-ZnIn2S4 / GCE in 5 mL of the above electrolyte, scan 7 cycles in the voltage range of -0.2 V to 1.7 V using cyclic voltammetry, take out the electrode, wash it with anhydrous ethanol and deionized water, and dry it to obtain [HOEMIM]BF4-PEDOT / [HOEMIM]BF4-ZnIn2S4 organic-inorganic hybrid photoelectric material.

[0060] Example 5

[0061] (i) preparing an electrolyte containing EDOT and [HOEMIM]PF6, wherein the solvent used is anhydrous acetonitrile, the concentration of EDOT is 5 mmol / L, and the concentration of [HOEMIM]PF6 is 2 mmol / L;

[0062] (ii) 5 μL of [HOEMIM]BF4-ZnIn2S4 prepared in Example 3 was drop-coated on the surface of a clean glassy carbon electrode (GCE) and dried;

[0063] (iii) Immerse the dried electrode [HOEMIM]BF4-ZnIn2S4 / GCE in 5 mL of the above electrolyte, scan 7 cycles in the voltage range of -0.2 V to 1.7 V using cyclic voltammetry, take out the electrode, wash it with anhydrous ethanol and deionized water, and dry it to obtain [HOEMIM]PF6-PEDOT / [HOEMIM]BF4-ZnIn2S4 organic-inorganic hybrid photoelectric material.

[0064] Example 6

[0065] (i) preparing an electrolyte containing EDOT and [HOEMIM]NTf2, wherein the solvent used is anhydrous acetonitrile, the concentration of EDOT is 5 mmol / L, and the concentration of [HOEMIM]NTf2 is 2 mmol / L;

[0066] (ii) 5 μL of [HOEMIM]BF4-ZnIn2S4 prepared in Example 3 was drop-coated on the surface of a clean glassy carbon electrode (GCE) and dried;

[0067] (iii) Immerse the dried electrode [HOEMIM]BF4-ZnIn2S4 / GCE in 5 mL of the above electrolyte, and scan 7 cycles in the voltage range of -0.2 V to 1.7 V using cyclic voltammetry. Take out the electrode, wash it with anhydrous ethanol and deionized water, and dry it to obtain [HOEMIM]NTf2-PEDOT / [HOEMIM]BF4-ZnIn2S4 organic-inorganic hybrid photoelectric material.

[0068] Figure 4These are scanning electron microscope images of [HOEMIM]BF4-PEDOT / [HOEMIM]BF4-ZnIn2S4, [HOEMIM]PF6-PEDOT / [HOEMIM]BF4-ZnIn2S4, [HOEMIM]NTf2-PEDOT / [HOEMIM]BF4-ZnIn2S4, and LiClO4-PEDOT / [HOEMIM]BF4-ZnIn2S4 obtained in Examples 4, 5, and 6 of the present invention. As can be seen from the figure, compared with LiClO4-PEDOT / [HOEMIM]BF4-ZnIn2S4 prepared with traditional supporting electrolyte (LiClO4), the PEDOT film layer prepared on the surface of [HOEMIM]BF4-ZnIn2S4 using ionic liquids [HOEMIM]BF4, [HOEMIM]PF6, and [HOEMIM]NTf2 as supporting electrolytes gradually becomes smooth, transparent and continuous, among which [HOEMIM]NTf2-PEDOT has the smoothest, continuous and transparent film layer structure characteristics.

[0069] Figure 5 These are the photocurrent response diagrams of [HOEMIM]BF4-PEDOT / [HOEMIM]BF4-ZnIn2S4, [HOEMIM]PF6-PEDOT / [HOEMIM]BF4-ZnIn2S4, [HOEMIM]NTf2-PEDOT / [HOEMIM]BF4-ZnIn2S4, LiClO4-PEDOT / [HOEMIM]BF4-ZnIn2S4 and [HOEMIM]BF4-ZnIn2S4 obtained in Examples 4, 5 and 6 of the present invention. As can be seen from the figure, PEDOT prepared using ionic liquids [HOEMIM]BF4, [HOEMIM]PF6, and [HOEMIM]NTf2 as supporting electrolytes has a very significant sensitization effect on [HOEMIM]BF4-ZnIn2S4, and the sensitization factor and the photocurrent of PEDOT / [HOEMIM]BF4-ZnIn2S4 change with the change of ionic liquids in the organic material PEDOT. The sensitization factors of the prepared [HOEMIM]BF4-PEDOT, [HOEMIM]PF6-PEDOT, and [HOEMIM]NTf2-PEDOT to [HOEMIM]BF4-ZnIn2S4 are about 52 times, 55 times, and 78 times, respectively. Among them, the sensitization effect of PEDOT prepared using [HOEMIM]NTf2 as the supporting electrolyte on [HOEMIM]BF4-ZnIn2S4 is the most significant, with a sensitization factor of about 78 times, the largest photocurrent and good stability.

[0070] Figure 66A and Mott-Schottky curves of the current-potential linear scanning curve (6A) and the Mott-Schottky curve (6B) of [HOEMIM]NTf2-PEDOT / [HOEMIM]BF4-ZnIn2S4 prepared in Example 6 of the present invention. Figure 6 A shows that the prepared [HOEMIM]NTf2-PEDOT / [HOEMIM]BF4-ZnIn2S4 produces obvious cathode photocurrent at a relatively negative potential, and produces obvious anode photocurrent at a relatively positive potential, indicating that a pn heterojunction may be formed between PEDOT and ZnIn2S4; Figure 6 B It can be seen that the prepared [HOEMIM]NTf2-PEDOT / [HOEMIM]BF4-ZnIn2S4 presents a "V"-shaped curve, which indicates that the positive slope and negative slope appear simultaneously in the PEDOT / ZnIn2S4 organic-inorganic hybrid photoelectric material, that is, the n-type and p-type coexistence characteristics of [HOEMIM]NTf2-PEDOT / [HOEMIM]BF4-ZnIn2S4, proving that a pn heterojunction is formed between PEDOT and ZnIn2S4.

[0071] Example 7

[0072] (i) preparing an electrolyte containing EDOT and [HOEMIM]NTf2, wherein the solvent used is anhydrous acetonitrile, the concentration of EDOT is 5 mmol / L, and the concentration of [HOEMIM]NTf2 is 2 mmol / L;

[0073] (ii) 5 μL of [HOEMIM]PF6-ZnIn2S4 prepared in Example 2 was drop-coated on the surface of a clean glassy carbon electrode (GCE) and dried;

[0074] (iii) Immerse the dried electrode [HOEMIM]PF6-ZnIn2S4 / GCE in 5 mL of the above electrolyte, and scan 7 cycles in the voltage range of -0.2 V to 1.7 V using cyclic voltammetry. Take out the electrode, wash it with anhydrous ethanol and deionized water, and dry it to obtain [HOEMIM]NTf2-PEDOT / [HOEMIM]PF6-ZnIn2S4 organic-inorganic hybrid photoelectric material.

[0075] Example 8

[0076] (i) preparing an electrolyte containing EDOT and [HOEMIM]NTf2, wherein the solvent used is anhydrous acetonitrile, the concentration of EDOT is 5 mmol / L, and the concentration of [HOEMIM]NTf2 is 2 mmol / L;

[0077] (ii) 5 μL of [HOEMIM]NTf2-ZnIn2S4 prepared in Example 1 was dropped onto the surface of a clean glassy carbon electrode (GCE) and dried;

[0078] (iii) Immerse the dried electrode [HOEMIM]NTf2-ZnIn2S4 / GCE in 5 mL of the above electrolyte, and scan 7 cycles in the voltage range of -0.2 V to 1.7 V using cyclic voltammetry. Take out the electrode, wash it with anhydrous ethanol and deionized water, and dry it to obtain [HOEMIM]NTf2-PEDOT / [HOEMIM]NTf2-ZnIn2S4 organic-inorganic hybrid photoelectric material.

[0079] Figure 7 These are the photocurrent response diagrams of [HOEMIM]NTf2-PEDOT / [HOEMIM]PF6-ZnIn2S4, [HOEMIM]NTf2-PEDOT / [HOEMIM]NTf2-ZnIn2S4, [HOEMIM]PF6-ZnIn2S4, and [HOEMIM]NTf2-ZnIn2S4 obtained in Examples 7 and 8 of the present invention. As can be seen from the figure, the PEDOT prepared using the optimal supporting electrolyte [HOEMIM]NTf2 also has a very significant sensitizing effect on ZnIn2S4 synthesized using [HOEMIM]PF6 and [HOEMIM]NTf2 as morphology regulators, and the sensitization effect and the photocurrent of [HOEMIM]NTf2-PEDOT / ZnIn2S4 change with the change of ionic liquid in the inorganic material ZnIn2S4. The sensitization multiples of the prepared [HOEMIM]NTf2-PEDOT to [HOEMIM]NTf2-ZnIn2S4 and [HOEMIM]PF6-ZnIn2S4 are about 11 times and 27 times, respectively.

[0080] The above is only a preferred embodiment of the present invention, which certainly cannot be used to limit the scope of rights of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and changes can be made without departing from the principle of the present invention, and these improvements and changes are also regarded as the protection scope of the present invention.

Claims

1. A PEDOT / ZnIn2S4 organic-inorganic hybrid photoelectric material, characterized in that: The invention comprises a ZnIn2S4 inorganic material, a PEDOT organic material deposited on the surface of the ZnIn2S4 inorganic material and an ionic liquid dopant, wherein the cation of the ionic liquid dopant comprises a 1-hydroxyethyl-3-methylimidazolium cation [HOEMIM] + , the anion of the ionic liquid dopant includes BF4 – PF6 – NTf2 – at least one of anions; First, ionic liquid is prepared to regulate ZnIn2S4, and then PEDOT film is prepared on the surface of ZnIn2S4 by electrochemical polymerization using ionic liquid.

2. The PEDOT / ZnIn2S4 organic-inorganic hybrid photoelectric material according to claim 1, characterized in that: The PEDOT / ZnIn2S4 hybrid material in the PEDOT / ZnIn2S4 organic-inorganic hybrid photoelectric material has a pn heterojunction structure.

3. The PEDOT / ZnIn2S4 organic-inorganic hybrid photoelectric material according to claim 1, characterized in that: The ZnIn2S4 inorganic material is in the shape of a flower ball, and the deposition thickness of the PEDOT organic material is 20-40nm.

4. A method for preparing a PEDOT / ZnIn2S4 organic-inorganic hybrid photoelectric material as claimed in any one of claims 1 to 3, characterized in that: The following steps are involved: a. Dissolve zinc salt, indium salt and ionic liquid in water, and stir at room temperature until the mixture is uniform to obtain a mixed solution; b. Add thioacetamide (TAA) to the solution obtained in step a, and continue stirring at room temperature until the mixture is uniformly mixed; c. The solution obtained in step b is reacted at 140-180° C. and then cooled naturally; d. washing and drying the solid product obtained in step c to obtain an inorganic material; e. Prepare electrolyte of EDOT and ionic liquid; f. Electrochemically polymerizing PEDOT using the electrolyte prepared in step e on the electrode surface on which the inorganic material is drop-coated, to prepare PEDOT / ZnIn2S4 organic-inorganic hybrid photoelectric material.

5. The method for preparing the PEDOT / ZnIn2S4 organic-inorganic hybrid photoelectric material according to claim 4, characterized in that: In the step a, in the mixed solution, Zn 2+ WithIn + The molar ratio of Zn is 1:

2. 2+ The molar ratio of the deionized liquid to the ionic liquid is 1:10-40, and the concentration of the deionized liquid in the system is 10-40 mmol L -1 .

6. The method for preparing the PEDOT / ZnIn2S4 organic-inorganic hybrid photoelectric material according to claim 4, characterized in that: In the step a, the ionic liquid is at least one of [HOEMIM]NTf2, [HOEMIM]PF6, and [HOEMIM]BF4.

7. The method for preparing the PEDOT / ZnIn2S4 organic-inorganic hybrid photoelectric material according to claim 4, characterized in that: In the step b, thioacetamide and Zn 2+ The molar ratio is 4:

1.

8. The method for preparing the PEDOT / ZnIn2S4 organic-inorganic hybrid photoelectric material according to claim 4, characterized in that: In the step e, the solvent used to prepare the electrolyte is anhydrous acetonitrile, the molar ratio of the ionic liquid to EDOT in the electrolyte is 1-6:5, and the concentration of EDOT is 3-7 mmol / L.

9. The method for preparing the PEDOT / ZnIn2S4 organic-inorganic hybrid photoelectric material according to claim 4, characterized in that: In the step e, the ionic liquid is at least one of [HOEMIM]NTf2, [HOEMIM]PF6, and [HOEMIM]BF4.

10. The method for preparing the PEDOT / ZnIn2S4 organic-inorganic hybrid photoelectric material according to claim 4, characterized in that: In the step f, the specific method of electrochemically polymerizing PEDOT is to immerse the electrode coated with inorganic material in the electrolyte prepared in the step e, and use cyclic voltammetry to electrochemically polymerize 5-9 cycles in the range of -0.2-1.7 V to prepare PEDOT, thereby obtaining PEDOT / ZnIn2S4 organic-inorganic hybrid photoelectric material.